INTERPRETASI PROMOSI SECARA PERSONAL SELLING DALAM EKSPLANASI PENJUALAN PRODUK SIARAN TELEVISI DIGITAL PT. SIBAYAK ENTERTAINMENT INDONESIA - Agus Nakkok Simanjuntak; Anita Tresia Samosir; Desi N Hutahaean (LPPM Universitas HKBP Nommensen, 2021)
PT. Sibayak Entertainment is a company that markets television broadcasts that subscribe to broadcasting on a prepaid basis with K-Vision satellite digitally through Kompas Gramedia Televison Group. Marketing is carried out by personal selling or with the aim that television broadcast marketing can be carried out in two directions and is considered more effective in marketing products, because the final goal is sales. This research was conducted using a descriptive qualitative analysis method based on the results of the questionnaire scores by collecting scores from the questionnaire, processed by recapitulation scores, ideally scores and percentage scores of respondents in this case personal selling and sales achievement of digital TV broadcasts in Karo Regency, North Sumatra Province. PT. Sibayak Entertainment Indonesia with personal selling has the greatest influence on sales achievement, with a total sample of 50 respondents. Based on research that has been done using the results of respondents' answers, 80% to 90% of respondents gave answers agree and strongly agree, the rest there are still disagree and strongly disagree with promotions using personal selling as well as sales achievements. By using the recapitulation and percentage of strengths and weaknesses, personal selling and sales achievements are in the strong and very strong categories. This shows that PT. Sibayak Entertainment Indonesia has chosen a good promotion step by using personal selling because it shows good sales achievements and sales targets can be achieved as determined by the company.